Silica‐Supported Phosphine–Gold Complexes as an Efficient Catalytic System for a Dearomative Spirocyclization. Issue 1 (30th November 2020) - Cao, Zhen; Scalabre, Antoine; Nlate, Sylvain; Buffière, Sonia; Oda, Reiko; Pouget, Emilie; Bibal, Brigitte
Abstract: The combination of metal catalyst and inorganic silica frameworks provides a greener approach to recyclable catalysis. In this study, three phosphine–gold chloride complexes have been successfully covalently grafted onto chiral silica nanohelices. The resulting 3D ensembles showed chiroptical properties that allowed the monitoring of the supported ligands. The heterogeneous gold chloride catalysts in cooperation with silver triflate exhibited high reactivity in various reactions, especially in the spirocyclization of aryl alkynoate esters, for which a catalytic loading of 0.05 mol % could be employed. The heterogeneous catalysts could be easily recovered and recycled seven or eight times without any loss of efficiency. By adding more silver triflate, 25 cycles with full conversion were achieved owing to a complex catalytic system based on silica and metallic species. Abstract : Working together ! Phosphine–gold complexes grafted onto chiral silica nanohelices, in cooperation with silver triflate, exhibit a high reactivity in various reactions, including the spirocyclization of aryl alkynoate esters. The heterogeneous catalysts could be easily recovered and recycled for up to 25 cycles without any loss of efficiency by adding more silver triflate every seventh cycle. A complex catalytic mechanism based on silica and metallic species is probably responsible for the high efficiency.